Arbuscular mycorrhizal fungi enhanced rice proline metabolism under low temperature with nitric oxide involvement - Liu, Zhilei; Bi, Shiting; Meng, Jingrou; Liu, Tingting; Li, Pengfei; Yu, Cailian; Peng, Xianlong (Frontiers in Plant Science, 2022)
Arbuscular mycorrhizal fungi (AMF) are known to improve plant stress tolerance by regulating proline accumulation, and nitric oxide (NO) plays an important signaling role in proline metabolism. Environmental nitrogen (N) affects AMF colonization and its contribution to host plants resistance to stress conditions. However, the relationship between proline metabolism and NO in mycorrhizal rice and the effect of N application on symbiont proline metabolism under low temperature have not been established. Pot culture experiments with different temperature, N and exogenous NO donor treatments were conducted with non-mycorrhizal and mycorrhizal rice. The results showed that AMF enhanced rice proline accumulation under low-temperature stress and decreased glutamate (Glu) and ornithine (Orn) concentrations significantly. In comparison with non-mycorrhizal rice, AMF colonization significantly decreased the Glu concentration, but had little effect on the Orn concentration under low-temperature stress, accompanied by increasing expression of OsP5CS2, OsOAT and OsProDH1. Exogenous application of NO increased proline concentration both under normal and low temperature, which exhibited a higher increase in mycorrhizal rice. NO also triggered the expression of key genes in the Glu and Orn pathways of proline synthesis as well as proline degradation. Higher N application decreased the AMF colonization, and AMF showed greater promotion of proline metabolism at low N levels under low temperature stress by regulating the Glu synthetic pathway. Meanwhile, AMF increased rice nitrate reductase (NR) and nitric oxide synthase (NOS) activities and then enhanced NO accumulation under low N levels. Consequently, it could be hypothesized that one of the mechanisms by which AMF improves plant resistance to low-temperature stress is the accumulation of proline via enhancement of the Glu and Orn synthetic pathways, with the involvement of the signaling molecule NO. However, the contribution of AMF to rice proline accumulation under low-temperature stress was attenuated by high N application.